Strategic Approach for Controlling Soil and Groundwater Contamination in Urban and Rural Areas of Nigeria - Oyebode, O. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Soil pollution and groundwater contamination are rampant in urban and rural areas of various developing countries including Nigeria. The quality of groundwater is a vivacious concern for human beings since it is directly associated with the human welfare and it is needed to conserve water resources. This paper x-rays strategic approach for controlling soil and groundwater contamination to enhance the efficiency of civil and environmental engineering design through recent trends and practice which will play a vital role in handling environmental pollution. Strategic approach highlighted involves the formulation and implementation of the major goals and initiatives based on consideration of resources and an assessment of the internal and external environments in which the organization competes. One or more of these approaches are often combined for more cost-effective treatment. The field studies for assessment of contamination comprised of detailed hydro-geological investigations which include geophysical investigations, borehole drilling, development of monitoring wells, followed by collection and analysis of existing field samples (dumpsite, subsurface soil and groundwater) are very critical for efficient handling of environmental pollution. It has been concluded that basic necessities for a healthy environment and public health include clean air, safe and sufficient water Safe and adequate food, safe and peaceful settlements, stable global environment in order to achieve excellent public health without soil pollution and groundwater contamination. Strategic approaches to remediation of contaminated soils include isolation, bioremediation, immobilization, toxicity reduction, physical separation and extraction.